Pelatihan Pengolahan Sampah Botol Kaca dengan Teknik Decoupage di Desa Cibitung Wetan, Kabupaten Bogor - Yunita Fitra Andriana; Bayyinah Nurrul Haq; Ulfa Septiana (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2021)
This community service activity, which was carried out in Desa Cibitung Wetan, Kabupaten Bogor, aims to increase the skills of housewives in processing glass bottles waste into flower vases. The Posdaya in that village has a waste bank program that has been running well. One of the programs carried out routinely at the waste bank is sorting unorganic waste that can be recycled. Even so, after this sorting process a series of further processing is needed. The method used in this activity is a short training by providing special skill, which is decoupage technique. The training started with giving demonstrations, then continued with hands-on practice and ended with discussion session. Participants in this training activity consisted of housewives who were members of Posdaya. They come from families with middle to lower economic backgrounds. The skills given in this training are expected to increase the creativity of the participants in processing waste into products with selling value, so as it is able to increase family income. Keywords: Waste Processing, Selling Value Products